Designing of Yogurt Packaging Product Using Quality Function Deployment Technique (Case Study at UMKM Ceriyogurt) - Putri, Nabila Tetrania; Oktavia, Rakhma (Sustainable Environmental and Optimizing Industry Journal, 2023)
Yogurt is a dairy product made through a fermentation process. Currently, yogurt packaging uses bottle-shaped plastic material. The current problem with yogurt packaging is that the visual image of the packaging, packaging shape, material thickness, packaging size and completeness of the packaging label is still low, so it is considered that it does not meet customer needs. Currently, yogurt packaging uses bottle-shaped plastic material. The problem of yogurt packaging is that the visual image of the packaging, packaging shape, material thickness, packaging size and completeness of the packaging label is still low, so it is considered that it does not meet customer needs. This research aims to identify a list of customer needs, a list of technical characteristics, directions of improvement, and the priority of technical characteristics of Yogurt product packaging. The research methodology uses the Quality Function Deployment (QFD) technique with the House of Quality (HOQ) matrix. The research generates 5 customer needs which were interpretated into 7 technical characteristics with directions for improvement, namely increased material thickness, fixed packaging volume size, reduced packaging length, reduced packaging width, reduced packaging height, improved visual image design, and increased label component completeness. The House of Quality produces a priority order of improvement, with the weight of importance of each technical characteristic, namely packaging length (90), packaging width (90), packaging height (90), packaging volume size (60), visual image size (60), completeness of label components (60), and thickness of packaging material (45).